Objective-C programmer's reference - Oliveira, Carlos (Apress Imprint: Apress, 2013)
Objective-C Programmer's Reference provides the tools necessary to write software in Objective-C-the language of choice for developing iOS and OS X applications. Author Carlos Oliveira begins from the basic building blocks of the language. He shows how to create correct and efficient applications by applying your knowledge of object-oriented and structured programming. This book: Takes you quickly through fundamental concepts such as interfaces and class implementations. Provides a concise reference to the Foundation Framework that is all-important when programming in Objective-C. Highlights key differences between Objective-C and other popular languages such as Java or Python. Provides the fundamentals of Cocoa and Cocoa Touch, which are the standard for OS X and iOS development. Objective-C Programmer's Reference makes extensive use of concepts already mastered by developers who are fluent in other languages such as C++, Java, Perl, and Python. The author's approach is logical and structured, and even novice developers will have an easy time absorbing the most important topics necessary to program in Objective-C. Objective-C Programmer's Reference is a book for professional developers in Objective-C, or those who are moving to Objective-C from other languages. The book is written for readers who lack the time to invest in more traditional books, which usually spend hundreds of pages to explain concepts that are part of the working programmer's standard vocabulary.